Adaptation Strategies of Pemuda Kreatif Art Studio in Preserving Senandung Bertelur Kau Sinangin as the Malay Traditional Art in Tanjungbalai City in Modern Context - Anshor, Arrini Shabrina; Triyanto, Triyanto (Catharsis, 2018)
Senandung Bertelur Kau Sinangin is a traditional music which is used by sailors before sailing. They sing and hit the drum as a ritual to get a lot of fish. They believe that the lyrics and the music which they sing can call the wind which lead them to the fish. This research projects the adaptation strategies of Pemuda Kreatif art studio in preserving the tradition. It employed qualitative method with interdisciplinary approach. The data were collected from observation, interview, and literature review. Then, they were validated by source’s triangulation. The analysis of the data use Miles and Huberman’s technique. The findings unveiled that the strategies planned by Pemuda Kreatif in preserving Senandung Bertelur Kau Sinangin in Tanjungbalai city was through (1) learning process and (2) cultural modification.